2014
DOI: 10.1177/1091581814540481
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sublethal Exposure to a Glyphosate-Based Herbicide Formulation on Metabolic Activities of Different Xenobiotic-Metabolizing Enzymes in Rats

Abstract: The activities of different xenobiotic-metabolizing enzymes in liver subcellular fractions from Wistar rats exposed to a glyphosate (GLP)-based herbicide (Roundup full II) were evaluated in this work. Exposure to the herbicide triggered protective mechanisms against oxidative stress (increased glutathione peroxidase activity and total glutathione levels). Liver microsomes from both male and female rats exposed to the herbicide had lower (45%-54%, P < 0.01) hepatic cytochrome P450 (CYP) levels compared to their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 57 publications
0
19
0
4
Order By: Relevance
“…As a consequence of liver intoxication, Roundup triggers the activation of xenobiotic-metabolizing enzymes. CYP1A1/2 and CYP3A dependent enzymes were inhibited in male rats from 0.7 ppm dissolved in water after a 90-day exposure (Larsen et al, 2014). Disruptions of CYP1A1/2 and CYP3A enzymes were observed at levels as low as 0.1 ppb in drinking water for a life-long exposure , and corroborated in hepatocyte cell lines (Gasnier et al, 2011).…”
Section: Peer-reviewed Literaturementioning
confidence: 81%
See 1 more Smart Citation
“…As a consequence of liver intoxication, Roundup triggers the activation of xenobiotic-metabolizing enzymes. CYP1A1/2 and CYP3A dependent enzymes were inhibited in male rats from 0.7 ppm dissolved in water after a 90-day exposure (Larsen et al, 2014). Disruptions of CYP1A1/2 and CYP3A enzymes were observed at levels as low as 0.1 ppb in drinking water for a life-long exposure , and corroborated in hepatocyte cell lines (Gasnier et al, 2011).…”
Section: Peer-reviewed Literaturementioning
confidence: 81%
“…Most of these studies were not chronic studies and were of short duration. Three studies even reported hepatorenal changes below the ADI at levels relevant for environmental exposures (Larsen et al, 2014;Larsen et al, 2012;Seralini et al, 2014a). However, their pharmacotoxicological relevance needs to be ascertained by replications.…”
Section: Commentary On Liver and Kidney Toxicitymentioning
confidence: 95%
“…These findings may be due to significant toxicity of additives (adjuvants or co-formulates) present in the pesticide preparations such as alcohol ethoxylates and alkylamine ethoxylates that enhance glyphosate stability and penetration into cell (Ibrahim, 2016 , respectively. Herbicide formulations containing ethoxytaled surfactants were found more toxic than glyphosate itself in different mammalian cell lines (Larsen et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…53 Doksan günlük 0,07 ppm glifosat maruziyeti de erkek sıçanlarda CYP1A1/2 ve CYP3A inhibisyonuna neden olmuştur. 54 EFSA'nın değerlendirmesine göre, sıçanlarda yürütülen uzun süreli çalışmalardan elde edilen bilgiler doğrultusunda gözlemlenen ters etki seviyesi (NOAEL) 100 mg/kg/gün, ters etki gösteren en düşük seviye (LOAEL) ise 350 mg/kg/gün olarak bulunmuştur. 55 …”
Section: 51unclassified